Penipuan Status Lajang Suami sebagai Bentuk Dharar dan Implikasinya terhadap Gugatan Cerai Istri: Analisis Kompilasi Hukum Islam - Wike Sundari; Heri Firmansyah (MAN 4 Kota Pekanbaru, 2026)
Marriage in Islam is a mitsaqan ghalizhan grounded in honesty and transparency. However, some husbands fraudulently claim to be “single” to conceal an existing marriage, facilitate siri marriages, or evade responsibilities. This study examines the legal construction of such fraud through the concepts of dharar and dhirar, and its implications for a wife’s divorce claim under the Compilation of Islamic Law (KHI). Using normative legal research with statutory and conceptual approaches, the study analyzes relevant legal norms and Islamic legal principles through a literature review. The findings indicate that false single-status claims are not merely administrative violations, but constitute dharar ma‘nawi (psychological and moral harm) that undermines marital integrity and violates the wife’s rights. In Islamic legal reasoning, this conduct falls under the maxim la dharar wa la dhirar. Juridically, it supports divorce claims through an expanded interpretation of Article 116 (f) and 116 (g) KHI.